Algae of forest floor in artificial hardwood stands in Zaporizhia region (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The species composition of algae forest floor in artificial oak and silver-chain plantations in Zaporizhia region was studied. Found 65 species of algae, including Chlorophyta – 41 species, Cyanophyta – 11, Xanthophyta – 7, Bacillariophyta – 4 and Eustigmatophyta – 2. The basis of algae communities are representatives of Phormidiaceae, Pleurochloridaceae, Chlamydomonadaceae, Bracteacoccaceae, Myrmeciaceae and Chlorellaceae. Analysis of ecological structure of investigated algae showed a significant predominance of edaphophilic species. Data of the vertical distribution of algae in the profile of forest floor and seasonal changes in the structure algae communities is provided.
Keywords: algae, forest floor, steppe, algae community.